PERILAKU BELAJAR MAHASISWA PROGRAM STUDI S1 AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS BRAWIJAYA - Yunita, Anne; Ludigdo, Ak., CA, Prof. Dr. Unti (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this study is to know about student learning behavior patterns in accounting bachelor’s degree of Economics and Business Faculty, Brawijaya University. The informants in this study amounted to 6 students who are grouped to Grade Point Average (GPA) below 3,0; between 3,0 to 3,5; and also more than 3,5. The data that used are the primary data, retrieved by using interview method. The  type  of  this  research  is  a  descriptive  research which  is  try  to  discover  the learning  behavior’s  phenomenon  of  three  student  types  that  are  study  oriented, hedonic, and activists. The result of  this study  indicate  that basically  the student behavior  is  extremely  diverse.  So,  the  grouping  of  students  cannot  always  be identical  with  a  high  or  low  Grade  Point  Average  (GPA).  Beside  that,  the grouping of students also cannot always be identified with their learning behavior patterns. Keywords:  behavioral  learning,  grouping  of  students,  accounting  bachelor’s degree